2014
DOI: 10.1364/ol.39.005566
|View full text |Cite
|
Sign up to set email alerts
|

Temporal soliton excitation in an ε-near-zero plasmonic metamaterial

Abstract: The excitation of temporal solitons in a metamaterial formed by an array of ε-near-zero (ENZ) plasmonic channels loaded with a material possessing a cubic (χ(3)) nonlinearity are theoretically explored. The unique interplay between the peculiar dispersion properties of ENZ channels and their enhanced effective nonlinearity conspires to yield low threshold intensities for the formation of slow group velocity solitons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 20 publications
(27 reference statements)
0
21
0
Order By: Relevance
“…This is confirmed by our measured CCD images (shown in Figure 3a sequence, the transmission of the signal light began to decrease. The resonance response of nanocavity A was affected greatly by the refractive index variation of the ambient dielectric material deposited on its surface, which is confirmed by the measurements of Kuramochi et al and Leuthold et al [28,29] According to the third-order nonlinear optical Kerr effect, the effective refractive index n of the nonlinear optical material can be calculated by the relation [25,30] n = n 0 + n = n 0 + n 2 I…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…This is confirmed by our measured CCD images (shown in Figure 3a sequence, the transmission of the signal light began to decrease. The resonance response of nanocavity A was affected greatly by the refractive index variation of the ambient dielectric material deposited on its surface, which is confirmed by the measurements of Kuramochi et al and Leuthold et al [28,29] According to the third-order nonlinear optical Kerr effect, the effective refractive index n of the nonlinear optical material can be calculated by the relation [25,30] n = n 0 + n = n 0 + n 2 I…”
Section: Resultsmentioning
confidence: 54%
“…According to the third‐order nonlinear optical Kerr effect, the effective refractive index n of the nonlinear optical material can be calculated by the relation n=n0+Δn=n0+n2Iwhere n 0 and n 2 are the linear and nonlinear refractive indices of the nonlinear optical material, respectively; Δn is the change in the refractive index of the nonlinear material; and I is the pump intensity reaching the nonlinear optical material. According to our measurement, the monolayer‐graphene/nano‐Au:(Er 3+ :Al 2 O 3 ) cover layer had a positive effective nonlinear refractive index n 2 in the optical communication range.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the steady-state entangled state of the emitters placed inside the ENZ waveguide is robust enough to be observed experimentally by using second-order correlation function measurements because it persists over extended time periods and long distances. It is also demonstrated that the introduction of active (gain) media inside the plasmonic ENZ nanochannels can lead to perfect loss compensation of the inherent 28 (nonradiative) plasmonic losses that, subsequently, reduces decoherence and further boosts transient quantum entanglement. We envision that the presented passive and active ENZ mediated RET and entangled states will find applications in future quantum information and communications integrated systems on a chip [58,59], the design of new low-threshold subwavelength nanolasers [60], and the creation of ultrasensitive quantum metrology devices [61].…”
Section: Discussionmentioning
confidence: 99%
“…The proposed quantum ENZ metamaterial system can support efficient long-range resonance energy transfer (RET) and entanglement between quantum dipole emitters independent of their positions within the nanowaveguide, over extended time periods and long separation distances. It is comprised of an array of metallic waveguides that exhibit an effective ENZ response at their cutoff frequency in combination with enhanced and homogeneous electromagnetic fields inside their nanochannels [27][28][29][30][31][32]. These interesting features, combined with the strong omnidirectional resonant coupling at the ENZ frequency, are ideal conditions to boost coherent light-matter interactions along elongated regions and can increase the temporal and spatial coherence between different emitters leading to multi-qubit entanglement [33].…”
mentioning
confidence: 99%
“…Furthermore, the combination of the ENZ regime with nonlinearity benefits from the non‐resonant enhancement of the normal electric field component across the vacuum‐ENZ medium interface , producing intriguing effects like transmissivity directional hysteresis and enhancement of second and third harmonic generation . A different field enhancement mechanism has been identified within narrow ENZ plasmonic channels, which has been exploited to boost optical nonlinearities , to investigate temporal soliton excitation , and for the enhancement of second‐harmonic generation efficiency . Recently the existence of frozen light in ENZ media with cubic nonlinearity has been theoretically predicted .…”
Section: Introductionmentioning
confidence: 99%